Review of Theoretical Explanations of IPO Underpricing - Jamaani, Fouad; Alidarous, Manal (Journal of Accounting, Business and Finance Research, 2019)
Motivated by a lack of availability of theoretical review of Initial Public Offerings (IPO) underpricing, this paper recognized a lack of presentation of theoretical explanations of the phenomenon of IPO underpricing in the literature. This makes scholars and investors interested in IPO underpricing research to face difficulty when it comes to the decision to employ IPO underpricing models. Hence, this paper provides a concise but comparatively adequate review of competing IPO underpricing theories. This review covered 13 theoretical models based on information asymmetry, institutional explanations, ownership and control reasons, and behavioral explanations to elucidate the phenomenon of IPO underpricing. Based on this review, the authors found that the underpricing phenomenon is eventually elucidated by the existence of information asymmetry amongst key IPO parties including the issuing firm, the underwriter, and the investor. Across the 13 reviewed IPO underpricing theories, the Entrepreneurial Wealth Losses (EWL) theory emerges as a compelling asymmetric information model. This is because it solves the problem of information asymmetry between the issuer and investor while accounting for the endogenous relationship between underwriter reputation and IPO underpricing.